Strong summability of multiple Fourier series and Sidon-type inequalities - Kuznetsovci, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study different versions of strong summation of N-dimensional Fourier series over polyhedrons and related estimates for integral norms of linear means of the Dirichlet kernels (Sidon-type inequalities).